Doublesex and GATAβ4 synergistically regulate the sex-dimorphic expression of storage protein 1 in Bombyx mori. - Jiamin Yan; Haonan Dong; Tingting Tian; Chunxia Xiao; Yuanyuan Sun; Jing Gong; Qingyou Xia; Yong Hou (PLoS Genetics)
Sexually dimorphic traits are widespread in organisms and are crucial for reproduction and behavior. These traits are typically controlled by sex-specific genes. However, their regulatory mechanisms are complex and incompletely understood. In Bombyx mori, a group of sex-differential storage proteins (SPs) exists, with storage protein 1 (SP1) expressed exclusively in females. In this study, we used the CRISPR/Cas9 system to knock out the doublesex gene and found that SP1 expression was sharply upregulated in male doublesex mutants and downregulated in female doublesex mutants, which suggests that doublesex is a key factor in the sex-differential expression of SP1. Then, we revealed that the female-specific doublesex isoform (dsxF) bound to and activated the SP1 promoter more strongly than the male-specific isoform (dsxM). Meanwhile, a transcription factor named GATAβ4 was found to be involved in the regulation by doublesex. Overexpression of GATAβ4 in Bombyx mori larvae affected adult reproductive behavior and dramatically upregulated SP1 expression in males. Furthermore, GATAβ4 interacted with both dsxF and dsxM, promoting nuclear translocation of dsxM, which in turn inhibited GATAβ4 binding to the SP1 promoter. In total, we found that dsxM did not directly repress SP1 expression in males but instead cooperated with other transcription factors to regulate downstream gene expression. These findings provide new insights into the regulation of sex-specific genes and the mechanisms controlling dimorphic traits.